2018
DOI: 10.1071/ah16277
|View full text |Cite
|
Sign up to set email alerts
|

Self-management of health care: multimethod study of using integrated health care and supportive housing to address systematic barriers for people experiencing homelessness

Abstract: Objectives The aims of the present study were to examine tenants' experiences of a model of integrated health care and supportive housing and to identify whether integrated health care and supportive housing improved self-reported health and healthcare access. Methods The present study used a mixed-method survey design (n=75) and qualitative interviews (n=20) performed between September 2015 and August 2016. Participants were tenants of permanent supportive housing in Brisbane (Qld, Australia). Qualitative dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
0
11
1
Order By: Relevance
“…Finally, EOHC requires that an approach to and delivery of care be developed with input from all stakeholders, including people with lived experience, but also all members of the healthcare team from physicians and nurses to janitors and receptionists. A recent study has found that cross sector collaboration that provides integrated health care improved barriers to access and also enabled self-managed care [30]. These changes require leaders to engage not only with providers who are already advocates for equity-seeking populations, but also with those who are not.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, EOHC requires that an approach to and delivery of care be developed with input from all stakeholders, including people with lived experience, but also all members of the healthcare team from physicians and nurses to janitors and receptionists. A recent study has found that cross sector collaboration that provides integrated health care improved barriers to access and also enabled self-managed care [30]. These changes require leaders to engage not only with providers who are already advocates for equity-seeking populations, but also with those who are not.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic poor health can further contribute to the economically deprived social conditions that make people sick; the causes of the causes of poor health (Marmot, ). The interaction of chronic poor health and deep and persistent social disadvantage act as barriers for people using and benefiting from mainstream health and social care even when those resources do exists (Parsell et al, ). The high rates of poverty and racism experienced by Australia's Indigenous people constitute an additional barrier to access mainstream health and social care (Davy et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The Multidisciplinary Model is nested within three bodies of knowledge in the health and social science literature that highlights the structural mechanisms that contribute to exclusion and deprivation among sections of society. These are as follows: the social determinants of health framework that shows how social disadvantage drives poor health among excluded groups and health inequities in society (Marmot, ); literature highlighting the link between chronic poor health and socioeconomic disadvantage (Blyth et al, ); and research illustrating how the cumulative effect of persistent disadvantage and chronic poor health represent structural barriers that limit people's capacity to engage with and benefit from mainstream health and social care systems (Parsell, Have, Denton, & Walter, ).…”
Section: Conceptualising the Multidisciplinary Modelmentioning
confidence: 99%
“…The health impacts of homelessness are exacerbated because people experiencing homelessness are often excluded from proper health care. Research shows that the state of homelessness represents a barrier to accessing essential health care (Baggett et al, 2010) and it likewise subverts homeless people's capacity to control their health care (Parsell et al, 2018). The result of all this is that homelessness drastically reduces people's life expectancy: the OECD (2020, p. 3) estimates that people experiencing homelessness die "up to 30 years earlier than the general population on average.…”
Section: Introductionmentioning
confidence: 99%